Vascular Supply to the Liver: A Report of a Rare Arterial Variant - Peter B. Johnson; Shamir O. Cawich; Sundeep Shah; Michael T. Gardner; Patrick Roberts; Brian Stedman; Neil W. Pearce (Case Reports in Radiology)
In the classic description of hepatic arterial supply, the common hepatic artery originates from the coeliac trunk. However, there are numerous variations to this classic pattern. We report a rare variant pattern of hepatic arterial supply and discuss the clinical significance of this variation.